2017
DOI: 10.1089/dia.2017.0051
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Use of Continuous Glucose Monitoring in Adults with Type 1 Diabetes

Abstract: With the emphasis on intensive management of type 1 diabetes, data from studies support frequent monitoring of glucose levels to improve glycemic control and reduce glucose variability, which can be related to an increase in macro and microvascular complications. However, few perform capillary blood glucose that frequently. There are currently two available alternatives that this review will discuss, continuous glucose monitoring (CGM) and flash glucose monitoring. CGM has become an important diagnostic and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 40 publications
3
55
0
3
Order By: Relevance
“…Of note, we showed that patients who used CGMS (N = 4) had better glycaemic control, compared with those who did not, which was consistent with prior data from observational and randomized trial in patients aged >60 (65) years [15][16][17].…”
Section: Discussionsupporting
confidence: 88%
“…Of note, we showed that patients who used CGMS (N = 4) had better glycaemic control, compared with those who did not, which was consistent with prior data from observational and randomized trial in patients aged >60 (65) years [15][16][17].…”
Section: Discussionsupporting
confidence: 88%
“…Fourthly, as previously mentioned, CGM devices are often less accurate in the hypoglycaemia range and have a high false‐detection rate for nocturnal hypoglycaemia . Additionally, mean absolute relative differences between CGM readings and blood glucose readings remain between 9% and 14% . As well as the limiting impact of the accuracy of CGM devices, the patients in our study wore a CGM device for a relatively short period of time (seven days), while recent CGM guidelines call for two weeks of CGM data collection for analysis .…”
Section: Discussionmentioning
confidence: 75%
“…18 Additionally, mean absolute relative differences between CGM readings and blood glucose readings remain between 9% and 14%. 19 As well as the limiting impact of the accuracy of CGM devices, the patients in our study wore a CGM device for a relatively short period of time (seven days), while recent CGM guidelines call for two weeks of CGM data collection for analysis. 13 Despite these limitations, the major strength of the study is that it is one of the largest CGM-based studies of insulin treatment in T1D to date.…”
Section: Safetymentioning
confidence: 99%
“…CGM, including isCGM (hereafter, unless stated, CGM includes both rtCGM and isCGM), is being used by an increasing number of people with type 1 diabetes (T1D). 15,16 The key benefits of CGM include real-time data monitoring for people with T1D and access for them and their HCPs to complete glucose datasets 17 ; both of which help people to achieve their target time spent within the acceptable range (time in range [TIR]: 3.9-10.0 mmol/L [70-180 mg/dL]) and avoid hyper-and hypoglycemia. 18 Reductions in HbA 1c have been reported with CGM use in people on multiple daily injection (MDI) therapy, 19 and continuous subcutaneous insulin infusion therapy, 20 with reduced time spent in hypoglycemia, 20 and improved hypoglycemia awareness.…”
Section: Introductionmentioning
confidence: 99%